RESILIENSI GURU DITINJAU DARI RESILIENSI GURU DITINJAU DARI RESILIENSI GURU DITINJAU DARI RESILIENSI GURU DITINJAU DARI RESILIENSI GURU DITINJAU DARI RESILIENSI GURU DITINJAU DARI RESILIENSI GURU DITINJAU DARI RESILIENSI GURU DITINJAU DARI RESILIENSI GURU - Sembiring, Mimpin (IN VERITATE LUX, 2020)
This article aims to explain that resilience is a very basic psychological construct that every teacher should have for the success of their teaching and learning. Resilience is something that must be fought for continuously. It is a dynamic process that must be fought for all time. Apart from that, resilience is not something that can stand alone, it is the result of a collaboration of a number of factors. This article will explain three types of factors that are very strong in forming resilience. The three intended factors are: emotion awareness, emotion regulation, and self-transcence relationship. Emotion awareness makes a teacher always aware (in Javanese language) of every emotion in himself. With emotion regulation, a teacher always tries to regulate or control and direct his emotions towards positive things. However, in fact, quite a few emotions that we have realized cannot be easily controlled. Even when a teacher has received input from colleagues or from the school principal, emotions that have run high are still difficult to regulate. For this reason, teachers need a third factor, self-transcendence. With a transcendental relationship, teachers can ask for help from the God they believe in to regulate their emotions to be positive.